Assessment of the gas content of coal deposits and forecasting of manifestations of hazardous phenomena in the mines of Donbass (on the example of the mine named after Zasyadko) - I. D. Bagriy (Геофизический журнал, 2011)
The paper highlights the major scientific-methodological theses of the near-surface structural thermo-atmo-geo-chemical methods (STAGM) developed at the Institute of Geological Sciences (NAS of Ukraine) and the results of its implementation in the study of conformities of distribution of emanation and hydrocarbon gases and modern geodynamical activity at the Donbas coal deposits (Tomashivska and А. F. Zasyadkо mines). The research proves the expediency of applying struc-tural thermo-atmo-geo-chemical methods for the evaluation of methane-bearing structures of coal deposits of industrial сoal production (with methane as raw fuel material), as well as for forecasting the areas with potentially dangerous gas-dynamic processes.